Review of Marketing Science (De Gruyter, 2003)
Objective The Review of Marketing Science (ROMS) is a peer-reviewed journal whose mission is wide and rapid dissemination of cutting-edge quantitative research in marketing science and related disciplines.The journal's focus is on topics and approaches in marketing science. Marketing science as a discipline places high value on approaches rooted in mathematics, economic theory, econometrics, statistics, and data-driven approaches. The journal particularly encourages interdisciplinary and cross-disciplinary work from diverse fields, as long as they are related to marketing science and generate insights that can be useful to marketing academics, managers or practitioners. ROMS emphasizes substantive results that stimulate other researchers as they pursue their work. ROMS is especially interested in papers that are on topics that are under-represented in marketing and economics journals, topics and methods that might be considered controversial or too cutting-edge for other outlets, papers that report early but potentially underdeveloped results of substantial and time-sensitive nature, and papers that offer a broad overview of new and innovative topics or approaches that do not as of yet have an established base in the literature. The journal values two-directional rapid feedback between the editors and authors. While the review process is strictly double-blind, authors are encouraged to contact the journal, through the journal's email link, with questions regarding fit of papers and topics to the journal, questions seeking guidance, and communication pertaining to substance and methodology of technical nature. Young researchers will find a sympathetic hands-on non-adversarial editorial team that is deeply committed to their research objectives and success. Serious research will be met with sympathetic and helpful guidance. Senior researchers should view this journal as a community platform to pro